2018
DOI: 10.4103/ijo.ijo_93_18
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of simvastatin against ultraviolet B-induced corneal endothelial cell death

Abstract: Purpose:Excessive ultraviolet B (UVB) exposure causing corneal endothelium injury, including apoptosis, is a serious condition. Therefore, drugs that can inhibit apoptosis in corneal endothelial cells represent an effective strategy. Simvastatin is widely used as a specific inhibitor of 3-hydroxy-3-methyl-glutaryl-CoA reductase, can reduce levels of low density lipoprotein (LDL) cholesterol, and exerts anti-inflammatory effects. However, the protective effect of simvastatin on corneal endothelial cells remains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In the present study, the cells with UV-B exposure decreased VEGF-A concentration by 84%. Nevertheless, some studies showed that VEGF-A expression in the UV-B irradiated cornea was dramatically increased (7,12,26). An explanation for this contradictory results may be that UV-B radiation at a relatively high level (10 J cm À2 ) may seriously impair normal physiological function of cells and eventually lead to cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the cells with UV-B exposure decreased VEGF-A concentration by 84%. Nevertheless, some studies showed that VEGF-A expression in the UV-B irradiated cornea was dramatically increased (7,12,26). An explanation for this contradictory results may be that UV-B radiation at a relatively high level (10 J cm À2 ) may seriously impair normal physiological function of cells and eventually lead to cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, small molecular antioxidants and anti-inflammatory agents (e.g. ascorbic acid, citicoline, fucoxanthin, EGCG, rebamipide, carteolol, cis-UCA, curcumin, simvastatin, nicotinamide, nicotinamide mononucleotide and nicotinamide adenine dinucleotide) have been explored for UVB-induced cornea injuries (5)(6)(7)(8)(9)(10)(11)(12)(13). Among these compounds, cis-UCA (Fig.…”
Section: Introductionmentioning
confidence: 99%